Two HEmostasis Methods After TransradIal Catheterization: THEMATIC Randomized Clinical Trial. Issue 2 (March 2020) - dos Santos, Simone Marques; Wainstein, Rodrigo Vugman; Valle, Felipe Homem; Corrêa, Camille Lacerda; Aliti, Graziella Badin; Ruschel, Karen Brasil; Gonçalves, Sandro Cadaval; Wainstein, Marco Vugman; Rabelo-Silva, Eneida Rejane
Abstract : Objective: The aim of this study was to compare the effect of 2 hemostasis devices on the incidence of radial artery occlusion (RAO) after transradial cardiac catheterization. Background: Radial artery occlusion is the most prevalent ischemic complication after radial artery catheterization. There is still no predictive pattern of vessel patency assessment, and the comparative effectiveness of different hemostasis techniques has yet to be established. Methods: This study used a randomized clinical trial of adult patients undergoing transradial cardiac catheterization. Participants were randomized into an intervention group (hemostasis with the TR Band device) and a control group (hemostasis with a conventional pressure dressing). The primary end point was the incidence of RAO (at discharge and at 30 days post catheterization). Results: Among the 600 patients included (301 in the intervention group and 299 controls), immediate RAO occurred in 24 (8%) in the TR Band group and 19 (6%) in the pressure-dressing group; at 30 days, RAO was present in 5 patients (5%) in the TR Band group and 7 (6%) in the pressure-dressing group. On multivariate analysis, peripheral vascular disease was the only independent predictor of RAO at discharge and at 30 days. Conclusions The incidence of RAO was similar in patients who received hemostasis with a TR Band versus a pressure dressing after transradial cardiac catheterization.